2021
DOI: 10.1177/20552173211057110
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and outcomes of COVID-19 despite SARS-CoV-2 vaccination in people with multiple sclerosis

Abstract: Background Several studies have demonstrated reduced serological response to vaccines in patients treated with anti-CD20 agents. However, limited data exist surrounding the clinical effect of disease modifying therapy (DMT) use on vaccine efficacy. Objectives To investigate breakthrough coronavirus disease 2019 (COVID-19) in vaccinated people with multiple sclerosis (PwMS) on DMT. Methods PwMS on DMT diagnosed with COVID-19 after full vaccination were identified from an existing Cleveland Clinic COVID-19 regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 9 publications
(10 reference statements)
3
24
0
Order By: Relevance
“…In fact, while the infection rate is similar in the first and in the second four months after vaccination in patients on ocrelizumab and fingolimod, and consistently higher than in patients on other DMTs, the initial protective effect is vanishing with time for patients in the other DMTs group, who had a good level of antibody response four weeks after vaccination 1 . This study complements the information of previous studies reporting the antibody levels after anti-SARS-Cov-2 vaccination in pwMS on different DMTs [1][2][3][4][5][6][7] , suggesting that antibodies play a dominant role in preventing Covid-19 infections and their severe consequences.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In fact, while the infection rate is similar in the first and in the second four months after vaccination in patients on ocrelizumab and fingolimod, and consistently higher than in patients on other DMTs, the initial protective effect is vanishing with time for patients in the other DMTs group, who had a good level of antibody response four weeks after vaccination 1 . This study complements the information of previous studies reporting the antibody levels after anti-SARS-Cov-2 vaccination in pwMS on different DMTs [1][2][3][4][5][6][7] , suggesting that antibodies play a dominant role in preventing Covid-19 infections and their severe consequences.…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, there is also growing evidence that vaccinated pwMS treated with anti-CD20 generated robust virus specific CD4 and CD8 T cell responses [4][5] , while these are slightly reduced in fingolimod treated patients 5 . A preliminary follow-up study of 344 fully vaccinated pwMS on DMT reported 13 breakthrough infections, 10 of which were in patients on anti-CD20 therapy and the remaining 3 on fingolimod 6 , suggesting a relevant role of antibodies in preventing the infection. The French registry recently reported a case series of 18 pwMS who had Covid-19 after two doses of BNT162b2-vaccination, 13 of which treated with anti-CD20 and four with fingolimod 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is mandatory to monitor the incidence of breakthrough infections in pwMS, to better understand the role of humoral and cellular response to SARS-CoV-2 vaccination in preventing Covid-19 and its consequences. A preliminary follow-up study of 344 fully vaccinated people with multiple sclerosis on disease modifying therapy reported 13 breakthrough infections, 10 of which were in patients under anti-CD20 therapy and the remaining 3 on fingolimod 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in our small case series, we referred to treatment with monoclonal antibodies MS patients with high risk of severe COVID-19 outcomes, as a consequence of low vaccination response (using ocrelizumab and fingolimod) or absence of vaccination [ 2 , 3 ], concomitant disease and treatment (e.g., chemotherapy for lymphoma), and high disability [ 1 , [5] , [6] , [7] ]. As such, while we included a pool of at-risk patients, we showed that, following the use of monoclonal antibodies for COVID-19, all of them fully recovered, in the absence of COVID-19 long-term symptoms, monoclonal antibodies' side effects, or MS changes in terms of relapses or disability.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple sclerosis (MS)-related disability and comorbidities can increase the risk of severe coronavirus disease-2019 (COVID-19) outcomes from severe acute respiratory syndrome–related coronavirus (SARS-CoV-2) infection [ 1 ]. Also, some disease-modifying treatments (DMTs), including anti-CD20 monoclonal antibodies and sphingosine-one-phosphate (S1P) modulators, can reduce the response to anti-SARS-CoV-2 vaccination (i.e., reduced seroconversion and/or cellular response) [ [2] , [3] , [4] ], and can subsequently be responsible for more severe COVID-19 outcomes, including hospitalizations and intensive care unit admissions [ [5] , [6] , [7] ].…”
Section: Introductionmentioning
confidence: 99%